HICKAM'S DICTUM VERSUS OCKHAM'S RAZOR. Issue 12 (15th November 2016) - Marchant, R; Bunting, E; Barritt, AW; Good, CD; Adams, N; Merve, A; Wickremaratchi, MM
Abstract : A 56-year-old man presented with evolving symptoms of left-sided weakness and fatigue over six months. Examination revealed spastic hemiparesis. MR brain imaging revealed confluent, oedematous white matter lesions in the right hemisphere without restricted diffusion or enhancement. Initial CSF analysis was unremarkable, including negative JC virus. Blood screen revealed a mild lymphopaenia. CT scanning of the viscera showed pulmonary changes which revealed, via transbronchial biopsy, non-caseating granulomata suggesting pulmonary sarcoidosis. High dose prednisolone was commenced following which the weakness improved. Methotrexate was initiated 3 weeks later, with the assumption the brain pathology was neurosarcoid. However, there then ensued a rapid deterioration with resurgence of left-sided weakness, difficulties within visuospatial, memory and executive cognitive domains and associated radiological progression. Urgent brain biopsy was arranged which showed numerous JC Virus particles within the parenchyma, consistent with progressive multifocal leukencephalopathy (PML). Repeat CSF analysis returned a now positive JC Virus PCR. Occult pulmonary sarcoidosis can be associated with immunoparesis and PML irrespective of immunosuppressive pharmacotherapy and necessitates a high index of suspicion.